Japanese stone gardens : origins, meaning, form - Mansfield, Stephen. (Tuttle Pub., 2009)
The text, complemented by abundant imagery, reveals the hidden order of stone gardens, heightening the enthusiast's awareness and appreciation of how they were constructed, and why. Fifteen gardens are featured in this book, some well-known, such as the famous temple gardens of Kyoto, others less so, among them gardens spread through the south of Honshu island and the southern islands of Shikoku and Kyushu and in faraway Okinawa--